2019
DOI: 10.1186/s13046-019-1145-8
|View full text |Cite
|
Sign up to set email alerts
|

NDR2 kinase contributes to cell invasion and cytokinesis defects induced by the inactivation of RASSF1A tumor-suppressor gene in lung cancer cells

Abstract: Background RASSF1A, a tumor suppressor gene, is frequently inactivated in lung cancer leading to a YAP-dependent epithelial-mesenchymal transition (EMT). Such effects are partly due to the inactivation of the anti-migratory RhoB GTPase via the inhibitory phosphorylation of GEF-H1, the GDP/GTP exchange factor for RhoB. However, the kinase responsible for RhoB/GEF-H1 inactivation in RASSF1A-depleted cells remained unknown. Methods NDR1/2 inactivation by siRNA or shRNA eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Epigenetic silencing of RASSF1A results in constitutive nuclear YAP11 accumulation, which increases the extracellular matrix deposition and enhances stem-like characteristics 39 . Consistent with previous studies 40,41 , our study confirmed that RASSF1A depletion induced YAP1 nuclear translocation and triggered the expression of its target genes. Nuclear YAP1 is believed to activate TEAD transcriptional activity and induce the expression of a broad range of cytokines 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Epigenetic silencing of RASSF1A results in constitutive nuclear YAP11 accumulation, which increases the extracellular matrix deposition and enhances stem-like characteristics 39 . Consistent with previous studies 40,41 , our study confirmed that RASSF1A depletion induced YAP1 nuclear translocation and triggered the expression of its target genes. Nuclear YAP1 is believed to activate TEAD transcriptional activity and induce the expression of a broad range of cytokines 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, exogenous RASSF1A expression caused a slight decrease in cell proliferation in H1299 cells ( Figure 4B) and A549 cells ( Figure 4C), the difference achieved being statistically significant only in A549 cells ( Figure 4C). This reflects the necessity of appropriate RASSF1A levels for efficient cell proliferation [5,32]. To the authors' surprise, in both H1299 and A549 cells, a single IAP-2 knockdown or a combined IAP-2 knockdown with RASSF1A re-expression caused a modest but significant reduction in cell proliferation ( Figure 4B-C).…”
Section: Iap-2 Interfering With Rassf1a-mediated Cell Proliferationmentioning
confidence: 92%
“…Additionally, a worse median OS was observed in patients with methylated RASSF1A treated with gemcitabine (30.3 months) compared to those treated with paclitaxel (70 months) [3]. These prognostic values of RASSF1A gene methylation were supported by data that demonstrated that RASSF1A restricts epithelial-mesenchymal transition (EMT) and cell invasion by controlling Yes-associated protein (YAP) nuclear shuttling and RhoB-regulated cytoskeletal remodeling process [4,5]. As such, RASSF1A inactivation favors the acquisition of a metastatic phenotype that explains these patients.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…RASSF1A depletion is notably associated with upregulation of Rac1 activity 46 , and direct interaction of RASSF1A with RhoA causes the suppression of RhoA transforming activity 71 . RASSF1A also modulates the activity of RhoB GTPase, which functions as RhoA/RhoC antagonists 72 , through fine-tuning GEF-H1 activity by inducing its phosphorylation via NDR2 kinase 56,73 . More recently, Rheb, a Ras-related small GTPase, was shown to form a complex with RASSF1A to coordinate Hippo and TOR signaling 74 .…”
Section: Rassf1a Structural Features and Principal Interacting Partnersmentioning
confidence: 99%